Kesiapan Usaha Mikro Kecil Menengah di Kecamatan Long Ikis Menghadapi Era Bisnis Digital - Agustino, Muhammad Rizqi Agustino; Susilo, Joko Hadi (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
The purpose of this study is to see the condition and readiness of MSME actors in Long Ikis Regency in entering the digital business era as well as identifying business insights and digital technology. The research method used was a qualitative method by conducting in-depth online interviews with 30 MSME actors randomly with various types of businesses in Long Ikis Regency, East Kalimantan Province. Using qualitative research methods, non-probability sampling with purposive sampling techniques, and qualitative descriptive research methods with a case study approach. The types of data in this study are primary data, and secondary data. The results of the study (1) MSME are interested in business digitalization, (2) MSME are starting to have digital business awareness, (3) technology support is not 100% as expected (4) there are 20% of MSME players who know Instagram business, 80% use Facebook (5) MSME need digital business introduction and development (6). MSME believe that the application of digital business has the potential to increase sales. The hope is that MSMEs can adapt and implement digital media optimally.